Respostas

2013-10-25T02:19:35-02:00
A) 7(x-9)-3(2x+9) = 4(-x+5)
7x-63-6x-27 = -4x+20
7x-6x+4x = 20+63+27
x+4x= 110
5x=110
x= 110/5
x= 22

B)
2(-2x+6)+4(5-7x)=5(-3x-4)
-4x+12+20-28x= -15x-20
-4x-28x+15x=12+20+20
-32x+15x=52
-17x=52
x=52/17
x=3,05
1 1 1
2013-10-25T10:07:27-02:00
A) 7(x-9)-3(2x+9)=4(-x+50
7x -63 -6x-27 =-4x +200
7x-6x+4x = 200+63 +27
5x=290
x=58

b)2(-2x+6)+4(5-7x)=5(-3x-4)
-4x+12 +20 -28x = -15x -20
-4x - 28x +15x = -20 -20 -12
-17x=-52 (-1) multiplica tudo por menos 1 para a letra ficar positiva
x= 52/17 

c)6(3x-5) - 5(2x+9)= - 6(2x+5)
18x -30 -10x -45= -12x-30
18x -10x +12x = 30 +45 -30
20x = 45
x= 45/20  simplificando por 5      x= 9/4